3D bioprinting for the construction of drug testing models-development strategies and regulatory concerns - Mallya, Divya; Gadre, Mrunmayi Ashish; Varadharajan, S.; Vasanthan, Kirthanashri S. (Frontiers in Bioengineering and Biotechnology, 2025)
A drug to be successfully launched in the market requires a significant amount of capital, resources and time, where the unsuccessful results in the last stages lead to catastrophic failure for discovering drugs. This is the very reason which calls for the invention of innovative models that can closely mimic the human in vivo model for producing reliable results. Throughout the innovation line, there has been improvement in the rationale in silico designing but yet there is requirement for in vitro-in vivo correlations. During the evolving of the drug testing models, the 3D models produced by different methods have been proven to produce better results than the traditional 2D models. However, the in vitro fabrications of live tissues are still bottleneck in realizing their complete potential. There is an urgent need for the development of single, standard and simplified in vitro 3D tissue models that can be reliable for investigating the biological and pathological aspects of drug discovery, which is yet to be achieved. The existing pre-clinical models have considerable drawbacks despite being the gold standard in pre-clinical research. The major drawback being the interspecies differences and low reliability on the generated results. This gap could be overcome by the fabrication of bioengineered human disease models for drug screening. The advancement in the fabrication of 3D models will provide a valuable tool in screening drugs at different stages as they are one step closer to bio-mimic human tissues. In this review, we have discussed on the evolution of preclinical studies, and different models, including mini tissues, spheroids, organoids, bioengineered three dimensional models and organs on chips. Furthermore, we provide details of different disease models fabricated across various organs and their applications. In addition to this, the review also focuses on the limitations and the current prospects of the role of three dimensionally bioprinted models in drug screening and development.